Review of Peter Maxwell Davies: Ave Maris Stella, Dark Angels, Five Klee Pictures, Miss Donnithorne’s Maggot, Stedman Doubles, Stevie’s Ferry to Hoy, Stone Litany, Symphony, Vesalii Icones, Westerlings, and Worldes Blis - Roberts, David (Contact: A Journal for Contemporary Music (1971-1990), 1978)
-